Increased Intestinal Permeability in Older Subjects Impacts the Beneficial Effects of Dietary Polyphenols by Modulating Their Bioavailability - Hidalgo-Liberona, Nicole; González-Domínguez, Raúl; Vegas, Esteban; Riso, Patrizia; Del Bo’, Cristian; Bernardi, Stefano; Peron, Gregorio; Guglielmetti, Simone; Gargari, Giorgio; Kroon, Paul Antony; Cherubini, Antonio; Andrés-Lacueva, Cristina (Journal of agricultural and food chemistry, 2020)
Polyphenols have great potential in regulating intestinal health and ameliorating pathological conditions related to increased intestinal permeability (IP). However, the efficacy of dietary interventions with these phytochemicals may significantly be influenced by interindividual variability factors affecting their bioavailability and consequent biological activity. In the present study, urine samples collected from older subjects undergoing a crossover intervention trial with polyphenol-rich foods were subjected to metabolomics analysis for investigating the impact of increased IP on the bioavailability of polyphenols. Interestingly, urinary levels of phase II and microbiota-derived metabolites were significantly different between subjects with healthier intestinal barrier integrity and those with increased IP disruption. Our results support that this IP-dependent impaired bioavailability of polyphenols could be attributed to disturbances in the gut microbial metabolism and phase II methylation processes. Furthermore, we also observed that microbiota-derived metabolites could be largely responsible for the biological activity elicited by dietary polyphenols against age-related disrupted IP.